A Randomized Controlled Trial in Obese Adults with Polycystic Ovarian Syndrome: Examining the Impact of Short-term Integrated Naturopathy and Yoga Interventions on Testosterone, Oxidative Stress, and Mental Health - Balakrishna Shetty; Geetha Balakrishna Shetty; H. L. Nanjeshgowda; Prashanth Shetty (International Journal of Yoga)
Background: Polycystic ovarian syndrome (PCOS) is a metabolic and endocrinological condition that affects many women of reproductive age. Pathology manifests as the changes in reproductive functions, encompassing disorders such as hyperandrogenism, irregular menstrual cycles, and insulin resistance with oxidative stress. We investigated the effect of naturopathy and yoga interventions on oxidative stress and androgens with metabolic parameters in patients with PCOS. Methods: We enrolled the 120 obese teenagers with PCOS, and we divided the patients into two groups as study (n = 60) and control (n = 60). In the study group, the patients were given 10 days of naturopathy and yoga interventions, whereas the other group was a waitlist control group. They were assessed for testosterone, lipid profile, malonaldehyde (MDA), total antioxidant capacity (TAC) with Hamilton Anxiety (HAM-A), and Depression (HAM-D) Scale at baseline and after 10 days of intervention. Results: We found out that the study group exhibited a significant decrease in testosterone, MDA, HAM-A, HAM-D, body mass index (BMI), and lipid profile compared to the control group also with an effective improvement in the TAC. The stepwise multiple regression data highlight that BMI as a significant predictor for the reduction of testosterone in PCOS after taking naturopathy and yoga interventions. Conclusion: The results indicate that short-term integrated yoga and naturopathy interventions are effective in modifying the disease progression of PCOS through endocrinological and metabolic balance.